Triple head-to-head comparison of fibrotic biomarkers galectin-3, osteopontin and gremlin-1 for long-term prognosis in suspected and proven acute heart failure patients. (15th January 2016) - Behnes, Michael; Bertsch, Thomas; Weiss, Christel; Ahmad-Nejad, Parviz; Akin, Ibrahim; Fastner, Christian; El-Battrawy, Ibrahim; Lang, Siegfried; Neumaier, Michael; Borggrefe, Martin; Hoffmann, Ursula
Abstract: Background: To comparatively evaluate long-term prognostic values of fibrotic biomarkers galectin-3, gremlin-1 and osteopontin in patients presenting to the emergency department (ED) suspected of acute heart failure (AHF). Methods: Patients with acute dyspnea or peripheral edema were enrolled in the ED. Biomarkers were measured and added to prognostic models including 11 conventional risk factors plus NT-proBNP assessing state-of-the-art statistics of discrimination, calibration, reclassification and Cox regression analyses. Prognostic outcomes were long-term all-cause mortality (ACM) and AHF-related rehospitalization (AHF-RH) at 1 and 5 years. Results: 401 patients including 122 AHF patients were enrolled (mean age 67 years, males 51%). During 5 years follow-up 129 patients (30%) died and 73 (18%) were re-hospitalized because of AHF. In multivariate analysis, galectin-3 (hazard ratios (HR) range 1.4–1.9; p = 0.03) and osteopontin (HR range 1.2–1.4; p = 0.001) remained associated with ACM overall and in the AHF population at 5 years, whereas gremlin-1 remained associated with AHF-RH at 1 year in AHF patients (HR 1.3; p = 0.002). ACM in whole cohort was best discriminated (AUC = 0.85, p = 0.0001), calibrated and re-classified (NRI + 0.50 to + 0.56, p = 0.0001) by galectin-3, whereas in AHF patients ACM was best discriminated by osteopontin (AUC range: 0.82–0.84, p = 0.0001; NRI + 0.34 to + 0.38, p < 0.1) and AHF-RH at 1 year by gremlin-1 (AUC range: 0.82–0.92, p = 0.0001; NRI + 0.59 to + 0.60, p = 0.006). Conclusions: A panel of fibrotic biomarkers, including osteopontin, galectin-3 and gremlin-1, might be useful for long term risk-stratification of symptomatic ED patients being suspected of AHF.